1994
DOI: 10.1038/bjc.1994.174
|View full text |Cite
|
Sign up to set email alerts
|

Expression of transforming growth factor α, amphiregulin and cripto-1 in human breast carcinomas

Abstract: Summary The expression of three epidermal growth factor (EGF)-related peptides, transforming growth factor a (TGF-a), amphiregulin (AR) and cripto-l (CR-1), was examined by immunocytochemistry (ICC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
91
0
5

Year Published

1994
1994
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(105 citation statements)
references
References 45 publications
9
91
0
5
Order By: Relevance
“…There is clear evidence for a role of amphiregulin in breast cancer initiation as well as progression (McBryan et al, 2008;Willmarth and Ethier, 2008). Amphiregulin is often overexpressed in mammary carcinoma (Qi et al, 1994) and generally higher in invasive breast carcinomas than in normal mammary epithelium (Panico et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…There is clear evidence for a role of amphiregulin in breast cancer initiation as well as progression (McBryan et al, 2008;Willmarth and Ethier, 2008). Amphiregulin is often overexpressed in mammary carcinoma (Qi et al, 1994) and generally higher in invasive breast carcinomas than in normal mammary epithelium (Panico et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of mRNA expression of the EGF family of ligands showed that both cell lines expressed high levels of AREG and modest amounts of HB-EGF and TGF-a. The coexpression of two or more EGF-like growth factors frequently occurs in human carcinomas (Ciardiello et al, 1991;Qi et al, 1994;Normanno et al, 2001). Yano et al, 2004;TfeltHansen et al, 2005b).…”
Section: Discussionmentioning
confidence: 99%
“…DISCUSSION Other than EGF or TGF-a, the role of additional EGF-related growth factors such as AR, heparin-binding EGF, or beta- cellulin in regulating the proliferation, differentiation, and transformation of mammary epithelial cells is relatively undefined (1,20). Like TGF-a, AR is expressed in both normal and transformed human mammary epithelial cells, in several human breast cancer cell lines, and in 40-80% of primary human breast carcinomas (11,13,14,18,19,21,22). Furthermore, both TGF-a and AR mRNA expression are induced after treatment with physiological, growth-promoting concentrations of 17p-estradiol in estrogen-responsive MCF-7 human breast cancer cells (18,23,24).…”
Section: Methodsmentioning
confidence: 99%